2021
DOI: 10.1108/lthe-09-2020-0038
|View full text |Cite
|
Sign up to set email alerts
|

Media students using mobile phones in the Arabian Gulf to improve English writing and video production skills

Abstract: Purpose A variety of alternate technology-enhanced teaching approaches are now available to university students to broaden their learning experiences and complement conventional face-to-face teaching. This paper aims to outline a study conducted at an English Medium Instruction (EMI) University in the Arabian Gulf where students were studying media. The study explored an innovative teaching approach that sought to enhance the students’ interaction with mobile phone applications as part of their learning experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Scholars have argued that Technology can be beneficial in language teaching and learning [ [39] , [40] , [41] , [42] ]. The integration of Technology can introduce innovative methods to language instruction, creating an active learning environment and increasing learner engagement [ [43] , [44] , [45] ]. Additionally, research has shown that positive perceptions of Technology are crucial for its effective use in instructional settings and for achieving desired learning outcomes [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars have argued that Technology can be beneficial in language teaching and learning [ [39] , [40] , [41] , [42] ]. The integration of Technology can introduce innovative methods to language instruction, creating an active learning environment and increasing learner engagement [ [43] , [44] , [45] ]. Additionally, research has shown that positive perceptions of Technology are crucial for its effective use in instructional settings and for achieving desired learning outcomes [ 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of artificial intelligence in recent years, many researchers and practitioners have been interested in technology integration to enhance the learning experience in general (e.g., AlSaied & Akhtar, 2021; Burkhart et al, 2020; Chang & Windeatt, 2021; Walker & Patel, 2018). Additionally, the Coronavirus disease 2019 (COVID-19) pandemic caused interruptions in educational systems worldwide, forcing them to integrate technology into the educational context, mainly through distance learning (e.g., Morgan, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, scholars were interested in students' perceptions of the FB types they receive in writing classes (e.g., Cohen & Cavalcanti, 1990;Hedgcock & Lefkowitz, 1996;Leki, 1991;Lizzio & Wilson, 2008;Peterson & Irving, 2008). More recently, several studies have explored learners' perceptions of learning contexts in general (e.g., Chien et al, 2020;Fu et al, 2019;Sletten, 2017;Wei & Chou, 2020), In this respect, several scholars have argued that technology can have a positive impact on language teaching and learning (e.g., Cheung & Slavin, 2012;Li, 2006Li, , 2021Zaini & Mazdayasna, 2015), and that its integration can allow for introducing more innovative methods to language teaching and learning and create an active learning environment, thus deepening the engagement of learners in the learning process (e.g., AlSaied & Akhtar, 2021;Chang & Windeatt, 2021;Walker & Patel, 2018). Further, the extant literature has found that positive perceptions of technology are necessary for future use in instructional settings and for achieving intended learning outcomes (e.g., Alzahrani & O'Toole, 2017;Joyce & Kirakowski, 2015;Wei & Chou, 2019), and can allow for deeper learning (Mohamed, 2008).…”
Section: Introductionmentioning
confidence: 99%